Analysis of the Public Procurement System in the Republic of Uzbekistan Problems and Current State - Rakhimjonov Kamronbek Ilxomjon ugli (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This article develops the theoretical and legal foundations of public procurement, research by foreign and domestic scientists, as well as scientific conclusions and recommendations for a more effective organization of the public procurement system in our country.